1500MPa-grade corrosion-resistant stainless steel for hot stamping forming of automobile parts
A 1500MPa-grade stainless steel with optimized chemical composition addresses the challenges of high strength and corrosion resistance, achieving cost-effective and environmentally friendly production for automotive components.
Patent Information
- Application Number
- CN202510171871.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-06-03
AI Technical Summary
Existing hot stamping steels face challenges in achieving high strength, corrosion resistance, and cost-effectiveness for automotive components, with traditional alloys being costly and environmentally harmful, and existing patents lacking clear guidance on achieving optimal mechanical and corrosion properties.
A 1500MPa-grade stainless steel with controlled chemical composition, including specific ranges of C, Cr, Nb, V, N, and other elements, optimized through thermodynamic calculations and high-throughput experiments to ensure full martensite structure and enhanced corrosion resistance, eliminating the need for costly coatings.
The steel achieves high strength, excellent corrosion resistance, and reduced production costs by avoiding costly coatings, suitable for automotive components with improved manufacturing efficiency and environmental sustainability.
Smart Images

Figure CN120082815A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of the development and application of martensitic stainless steel, and particularly relates to a 1500MPa-level corrosion-resistant stainless steel for hot stamping automotive parts. Background Art
[0002] Using hot stamping ultra-high strength steel for automotive parts is the only way to achieve lightweight and improve safety. The oxidation problem of traditional 1500MPa hot forming steel 22MnB5 during austenitization cannot be ignored. Currently, among the hot forming steel plates used globally, approximately half use Al-Si coatings to prevent oxidation and decarburization at high temperatures. However, the Al-Si coating has a high cost, and during the hot forming process, the coating will scale on the die surface, affecting the die life and increasing production costs. In addition, since carbon hot stamping forming steels such as 22MnB5 do not have corrosion resistance, painting protection is required when making automotive parts, which increases the production process and cost, and at the same time causes environmental pollution during the production process.
[0003] In recent years, with the implementation of the Carbon Border Adjustment Mechanism CBAM (also known as the EU carbon border tax), the green transformation of the automotive industry is imminent. In the future, the international automotive industry association will gradually start to promote the carbon labeling of products. Therefore, it has become an inevitable development trend for the automotive industry that green and low-carbon automotive steel products have market competitiveness. Stainless steel has attracted more and more attention from the automotive industry due to factors such as its low life cycle assessment (LCA). Stainless steel body and ultra-high strength stainless steel structural parts as the body framework have the advantages of high strength, corrosion resistance, and paint-free coating. It can not only reduce the process steps such as pickling, degreasing, phosphating, and painting during the body manufacturing process, but also greatly reduce the production and manufacturing costs, meeting the requirements of green environmental protection; at the same time, stainless steel can be recycled 100% without degradation, with extremely low metal loss during use, reducing environmental pollution caused by metal corrosion and deterioration, and having a lower overall life cycle application cost, and being more green and environmentally friendly.
[0004] Applying stainless steel to the hot stamping forming process needs to solve the contradiction between corrosion resistance and high-strength mechanical properties. Austenitic stainless steel has good corrosion resistance but low tensile strength, and cannot meet the ultra-high strength requirements of hot stamping forming. Ordinary 1Cr 13 、2Cr 13 Martensitic stainless steel can only reach 1300 - 1400MPa in strength through hot stamping forming, which cannot meet the ultra-high strength requirements; 3Cr 13 、4Cr 13Although martensitic stainless steels can reach the strength requirement of 1500 MPa level through hot stamping forming, they have insufficient ductility and poor corrosion resistance, and cannot meet the corrosion resistance requirements of green and low-carbon automotive parts. Although ultra-high strength and high toughness martensitic stainless steels used in aerospace and other fields can meet the requirements of ultra-high strength and corrosion resistance for hot stamping forming, these steels usually contain relatively high contents of precious alloy elements such as Cr, Ni, Mo, Co, Ti, etc., with high costs and cannot be widely applied to automotive hot stamping forming parts. PCT patent with application number 201880011193.7 discloses a "Steel for Manufacturing Parts by Hot Forming and Use of the Parts". This method describes the steel for manufacturing parts by stainless steel and the use of the parts. In this invention, it is defined that C ≤ 0.2%, Si ≤ 3.5%, Mn 1.5% - 16%, Cr 8% - 14%, Ni ≤ 6%, N ≤ 1%, Nb ≤ 1.2%, Ti ≤ 1.2%, Mo ≤ 2.0%, V ≤ 0.15%, Cu ≤ 2.0%, Al ≤ 0.2%, B ≤ 0.05%. The protection scope of this patent is too wide, while the examples are only applicable within a small range. The steel types described in this patent can be used for transportation components of vehicles, can also be used for rollover protection bars with high-strength collision safety, or complex structural components such as columns or fairings; even for anti-graffiti solutions, such as park benches, the surfaces of railways; and for tableware. This results in broad regulations on the composition and process in the patent, and does not clearly describe how to achieve the optimization design of specific mechanical properties, corrosion resistance and low-cost design through composition adjustment. At the same time, the steel contains relatively high contents of alloy elements such as Mo, Nb, Mn, Ti, etc., resulting in high costs; the corrosion resistance is not explained either.
[0005] In addition, there are few relevant patents and article reports on ultra-high strength stainless steels for hot stamping forming in automobiles at present. Therefore, developing a low-cost, green and low-carbon ultra-high strength corrosion-resistant stainless steel to meet the needs of automotive hot stamping forming parts has become a hot topic for countries to compete in developing. Summary of the Invention
[0006] The present invention provides a hot stamping stainless steel for automotive structural parts and welded parts with a tensile strength above 1500 MPa level and a pitting potential ≥ 0.05 V SCE and having good corrosion resistance. This new type of stainless steel has the characteristics of low cost, green environmental protection without plating, ultra-high strength, good corrosion resistance and high hardenability, etc., and can be suitable for industrial large-scale production of rolled hot-rolled sheets or cold-rolled sheets, and the hot stamping forming process fully meets the requirements of current hot forming production lines.
[0007] In order to achieve the above object, the present invention is realized by adopting the following technical solutions:
[0008] A 1500MPa - grade corrosion - resistant stainless steel for hot - stamping automotive parts, the chemical composition of the steel by weight percentage is: C: 0.05% - 0.20%, Si: 0.05% - 0.50%, Mn: 0.50% - 2.00%, P ≤ 0.020%, S ≤ 0.010%, Cr: 12.0% - 15.0%, V: 0.05% - 0.15%, Nb: 0.02% - 0.10%, Ni ≤ 1.00%, Cu ≤ 0.30%, Al < 0.05%, N: 0.01% - 0.10%, and the balance is Fe and inevitable impurity elements such as Mg, O, Ca, etc.
[0009] The Cr equivalent Creq in the steel = Cr% + Mo% + 1.5×Si% + 0.5×Nb% + 5×V% + 3Al is controlled within 15.0%.
[0010] The Ni equivalent Nieq in the steel = Ni% + 30×C% + 0.5×Mn% + 0.3×Cu% + 25N% + Co% is controlled within 8.0%.
[0011] The δ - phase formation temperature in the steel ≥ 1100°C, and the solution temperature of Nb(C, N) ≥ 1100°C.
[0012] Cr in the steel 23 C 6 and Cr x N y The solution temperature ≤ 950°C.
[0013] The solution temperature of V(C, N) in the steel ≥ 870°C.
[0014] The tensile strength of the stainless - steel plate ≥ 1500MPa, and the pitting potential ≥ 0.05V SCE .
[0015] The functions and control ranges of various elements in the stainless steel in the present invention are as follows:
[0016] 1) C is an austenite - forming element. Increasing the carbon C content can increase the δ - ferrite formation temperature and expand the austenite - phase region. In the present invention, to obtain a high - strength stainless steel mainly composed of martensite, considering the Schaeffler phase diagram, the Ni equivalent Nieq = Ni% + 30×C% + 0.5×Mn% + 0.3×Cu% + 25N% + Co% is controlled within 8.0%. At the same time, considering the low - cost factor, Ni addition is basically not considered in this steel, and the austenite - forming element function of C is fully utilized. In addition, C is an element for the formation of Cr 23 C 6 and increasing its content will increase Cr 23 C 6The formation temperature, reducing the content of solid-solution Cr element, seriously reduces the corrosion resistance of stainless steel, and is also adverse to plasticity and welding performance; conversely, reducing the C content will reduce the strength of stainless steel. Therefore, the selection of C content needs to take into account both corrosion resistance and mechanical properties. Combining thermodynamic calculations, the preferred control range of C content is 0.05% - 0.20%.
[0017] 2) Cr is the most important alloying element in stainless steel and plays a decisive role in corrosion resistance. Cr produces a dense Cr 2 O 3 oxide film on the surface of stainless steel, which plays a strong passivation role to achieve the purpose of corrosion resistance. In the present invention, it is first necessary to consider forming a dense Cr 2 O 3 oxide film on the surface of stainless steel. The minimum content of Cr in solid solution in the matrix needs to reach 12.0 wt.%. Secondly, Cr is a ferrite-forming element, which narrows the austenite region. According to the Schaeffler phase diagram, in order to obtain a single martensite structure to ensure high strength and reduce the formation of δ-ferrite or the content of retained austenite as much as possible, in the present invention, the Cr equivalent Creq = Cr% + Mo% + 1.5×Si% + 0.5×Nb% + 5×V% + 3Al is controlled within 15.0%. Combining thermodynamic calculations, the Cr content range is taken as 12.0% - 15.0%.
[0018] 3) The micro-alloying element Nb plays an important role in the present invention. Nb and C, N precipitate to form Nb(C, N) at high rolling temperatures, which not only plays a role in refining grains, but also improves strength and toughness. Due to the precipitation of Nb(C, N) at high temperatures, the content of solid-solution carbon is reduced, thereby reducing the formation temperature of Cr 23 C 6 、Cr x N y and other chromium carbonitrides. It is necessary to ensure that the formation temperature of Cr 23 C 6 、Cr x N y is reduced below the hot stamping temperature to ensure that more Cr elements are dissolved in the matrix to achieve the purpose of improving corrosion resistance. Considering the factors of strengthening and toughening and cost comprehensively, combining thermodynamic calculations, the reasonable control range of Nb in the present invention is 0.02% - 0.10%.
[0019] 4) V is another important micro-alloying element in the present invention. V precipitates V(C, N) at rolling or hot stamping forming temperatures, which can refine grains and martensite laths, and greatly improve strength and toughness. Similarly, the precipitation of V(C, N) reduces Cr 23 C 6 、Cr x N yThe forming temperature is thus ensured, guaranteeing the corrosion resistance. The reasonable control range of V in the stainless steel of the present invention is 0.05% to 0.15%.
[0020] 5) N is a strong austenite-forming element, which can replace Ni in stainless steel, greatly reducing the usage amount of Ni and having the advantage of low cost. The present invention makes full use of the precipitation strengthening effect of N and microalloying elements Nb and V to improve the strength, while strictly controlling the addition of excessive N content, because when the N content is too high, the precipitation temperature of Cr x N y will increase, that is, it is necessary to avoid the precipitation of Cr x N y at the hot stamping forming temperature, thereby reducing the solid solution amount of Cr and ensuring the corrosion resistance. Combining with thermodynamic calculations, the reasonable control range of N is 0.01% to 0.15%.
[0021] 6) Si, as a ferrite stabilizing element in stainless steel, makes a certain contribution to improving strength, oxidation resistance and corrosion resistance, and is also often present in stainless steel as a deoxidizer. In the present invention, considering the control requirements of Creq and the need to obtain martensite structure, the content of Si is controlled at 0.05% to 0.50%.
[0022] 7) Mn is a relatively weak austenite-forming element in stainless steel, but has a strong effect of stabilizing austenite. At the same time, as Mn increases, the strength of stainless steel increases. In the present invention, a certain content of Mn is added to ensure austenitization and improve strength. Combining with thermodynamic calculations, the reasonable control range of Mn is 0.50% to 2.0%.
[0023] 8) Ni is an important austenitizing element in stainless steel and has an important influence on improving strength and toughness. However, Ni is expensive. In order to maintain the low-cost competitiveness of automotive hot stamping parts and considering factors such as scrap steel smelting, the content of Ni is usually controlled within 1.00%.
[0024] 9) Cu, as a residual element brought in by scrap steel during the smelting of stainless steel in the present invention, although it makes a certain contribution to strength, it is not deliberately added as a strengthening element and is usually kept within 0.30%.
[0025] 10) Al is usually added as a deoxidizer in stainless steel. To ensure sufficient deoxidation and cost control in the steel of the present invention, the content of Alt is generally controlled within 0.05%.
[0026] 11) P and S are impurity elements, which are harmful to the toughness of stainless steel. In principle, the lower the better. Considering cost control and other factors, the present invention controls the contents of P and S as P ≤ 0.02% and S ≤ 0.010%.
[0027] The key alloy design concept of the present invention is in 1Cr13 , on the basis of 2Cr 13 , appropriate amounts of Nb and V microalloying elements and a certain content of N are added, and the hot stamping forming process is skillfully utilized to ensure high strength, toughness and corrosion resistance. During the heating, heat preservation and cooling processes of hot stamping forming, first, the formation of δ-ferrite is eliminated as much as possible to ensure the acquisition of a fully martensitic structure to maintain high strength; second, the microalloying Nb and V elements are fully utilized to form nano-scale Nb(C, N) and V(C, N) strengthening phases with C and N, further increasing the strength to above 1500 MPa; third, the Cr 23 C 6 , Cr x Ny and other chromium carbonitrides are dissolved, and the dissolved C and N are captured by Nb and V, thus greatly improving the corrosion resistance.
[0028] Based on the above overall design concept, combined with the Schaeffler phase diagram and Thermo-Calc thermodynamic calculations, for the key phases such as austenite, ferrite, and martensite at different compositions and temperatures, as well as Nb(C, N), V(C, N), Cr 23 C 6 , Cr x N y and other precipitation phases, the formation temperatures and quantities are calculated to establish the corresponding relationships between chemical elements and the key phases, precipitation formation temperatures and quantities, and these are used as the principles for screening chemical compositions and controlling their contents.
[0029] In order to meet the requirements of large-scale production for forging and hot rolling at temperatures above 1100 °C, the steel grade of the present invention needs to avoid the formation of δ-phase at high temperatures and make full use of the strengthening and grain refinement effects of Nb(C, N). Therefore, the δ-phase formation temperature and the Nb(C, N) solution temperature ≥ 1100 °C; to ensure that Cr 23 C 6 , Cr x N y are fully dissolved, reducing the consumption of Cr elements to meet the requirement of improving corrosion resistance, the solution temperature of Cr 23 C 6 , Cr x N y needs to be ≤ 950 °C; in addition, to make full use of the precipitation strengthening effect of V(C, N), the solution temperature of V(C, N) needs to be higher than 870 °C.
[0030] In addition, in order to solve the problems of high cost and low efficiency caused by a large number of trial-and-error experimental studies in traditional component design, the present invention proposes a method for comprehensively calculating thermodynamics and assisting rapid screening of components through high-throughput experiments. This method is used to develop the 1500MPa grade corrosion-resistant stainless steel for hot stamping automotive components, and specifically includes the following method steps:
[0031] 1) By analyzing the application scenario requirements of the steel grade, collect the benchmark product system according to the product characteristics as the performance optimization benchmark; based on the requirements of high strength and high corrosion resistance after hot stamping, the target steel grade is mainly martensitic structure. Therefore, martensitic stainless steels 1Cr 13 and 2Cr 13 are used as the benchmark, and the corrosion resistance is improved by microalloying with N, Nb, and V.
[0032] 2) For the component system determined in step 1), use the thermodynamic software Thermo-Calc to call the multi-component iron-based thermodynamic database TCFE10 to calculate the phase diagram under relevant components; use thermodynamic calculation methods such as phase diagram data and equilibrium phase transformation principles, and the Schaeffler phase diagram to predict the phase composition and performance strengthening mechanism of the material under different temperature and component conditions, evaluate the coupling of the mechanical properties and application properties of different components, and preliminarily determine the high-performance (high strength, high corrosion resistance) material components.
[0033] 3) Based on the key phases that determine the mechanical properties and application properties determined in step 2), name them characteristic parameters, and then use the kinetic simulation software DICTRA. Based on the phase diagram thermodynamic database TCFE10 and the diffusion kinetics database MOBFE5, calculate the phase transformation temperature, phase ratio, second-phase precipitation temperature, and phase transformation process of the material. Combining the strength and toughness mechanism and corrosion resistance mechanism of the material, provide specific material component screening criteria, so as to obtain the optimized component range.
[0034] 4) Use the component optimization results determined in step 3) to quickly and low-costly carry out high-throughput experiments such as smelting, hot rolling, cold rolling, and heat treatment using a small-scale vacuum induction melting furnace, obtain the actual experimental data of the mechanical properties and pitting corrosion properties of the hot stamping process, and further verify and optimize to obtain the final component system and process plan that meet the user's requirements.
[0035] Compared with the prior art, the beneficial effects of the present invention are:
[0036] 1) The steel grade of the present invention not only has high strength but also has good corrosion resistance. Combined with the corresponding hot stamping forming process, it is suitable for manufacturing components such as automotive structural parts, reinforcement parts, and safety parts, such as bumpers and B-pillar reinforcement parts.
[0037] 2) In the present invention, a certain amount of N element is added and dissolved in the matrix to improve the mechanical properties. Therefore, by adding an appropriate amount of N element to this steel type, the C content can be reduced, thereby improving the corrosion resistance and welding performance of the martensitic stainless steel. The N element has a tendency to replace Ni in the present invention and has the advantage of low cost.
[0038] 3) The high-strength and corrosion-resistant hot stamping stainless steel of the present invention has an antioxidant effect during the hot stamping process, without the protection of an Al-Si coating. Moreover, the corrosion resistance of the steel type itself enables the reduction of process steps such as pickling, degreasing, phosphating, and painting during the body manufacturing process, greatly reducing costs in the production and manufacturing links. It is a new type of green and environmentally friendly steel.
[0039] 4) The tensile strength of the stainless steel of the present invention reaches above the 1500 MPa level, and the pitting potential ≥ 0.05 V SCE , with good corrosion resistance. Description of the Drawings
[0040] Figure 1 It is a SEM micrograph of the 1500 MPa level hot stamping stainless steel of Example 1 of this application.
[0041] Figure 2 It is the electrochemical test curve of the 1500 MPa level hot stamping stainless steel of Example 1 of this application and the comparative example. Detailed Embodiments
[0042] The following further illustrates the detailed embodiments of the present invention in conjunction with the embodiments. The following embodiments are used to specifically illustrate the content of the present invention. These embodiments are only general descriptions of the content of the present invention and do not limit the content of the present invention.
[0043] The following describes a 1500 MPa high-strength hot stamping stainless steel plate for automotive parts and its research and development method according to an embodiment of this application.
[0044] A corrosion-resistant stainless steel of 1500 MPa level for hot stamping forming automotive parts, the chemical composition in the steel is calculated by weight percentage as follows: C: 0.05% - 0.18%, Si: 0.05% - 0.50%, Mn: 0.50% - 2.00%, P ≤ 0.020%, S ≤ 0.010%, Cr: 12.0% - 15.0%, V: 0.05% - 0.15%, Nb: 0.02% - 0.10%, Ni ≤ 1.00%, Cu ≤ 0.30%, Al < 0.05%, N: 0.01% - 0.10%, and the balance is Fe and inevitable impurity elements such as Cu, Mg, O, Ca, etc.
[0045] The Cr equivalent Creq in the steel is controlled within 15.0% by Cr% + Mo% + 1.5×Si% + 0.5×Nb% + 5×V% + 3Al. The Ni equivalent Nieq in the steel is controlled within 8.0% by Ni% + 30×C% + 0.5×Mn% + 0.3×Cu% + 25N% + Co%. The δ-phase formation temperature in the steel is ≥1100 °C, and the solution temperature of Nb(C, N) is ≥1100 °C. Cr 23 C 6 and Cr x N y have a solution temperature ≤950 °C. The solution temperature of V(C, N) in the steel is higher than 870 °C.
[0046] The microstructural photographs of the high-strength and high-corrosion-resistant hot-stamped stainless steel sheet prepared by this preparation method are as Figure 1 shown.
[0047] A method for rapid screening of components assisted by comprehensive thermodynamics calculation and high-throughput experiment, which is used for developing the 1500 MPa grade corrosion-resistant stainless steel for hot stamping forming automotive parts. The specific method steps are as follows:
[0048] 1) Experimental data collection, and determination of the chemical composition range of the experimental steel plate.
[0049] By analyzing the application scenario requirements of the steel grade, collecting the benchmark product system according to the product characteristics as the performance optimization benchmark; based on the requirements of high strength and high corrosion resistance after hot stamping, the target steel grade is mainly martensitic structure. Therefore, taking martensitic stainless steels 1Cr 13 and 2Cr 13 as the benchmark, and improving the corrosion resistance through N, Nb, and V microalloying.
[0050] 2) Thermodynamic calculation, empirical formula, and strengthening mechanism analysis to determine the phase composition and strengthening component types in this system.
[0051] For the component system determined in step 1), use the thermodynamic software Thermo-Calc to call the multi-component iron-based thermodynamic database TCFE10 to calculate the phase diagram under relevant components; use thermodynamic calculation methods such as phase diagram data and equilibrium phase transformation principle, and the Schaeffler phase diagram to predict the phase composition and performance strengthening mechanism of the material under different temperature and component conditions, evaluate the coupling of the mechanical properties and application properties of different components, and preliminarily determine the high-performance (high strength, high corrosion resistance) material components.
[0052] 3) Combine the heat treatment process to regulate the characteristic parameters through thermodynamic calculation, so as to optimize and screen the steel grade components.
[0053] Based on the key phases that determine the mechanical properties and application properties in step 2), name them as characteristic parameters, and then use the kinetic simulation software DICTRA. Based on the phase diagram thermodynamic database TCFE10 and the diffusion kinetics database MOBFE5, calculate the phase transformation temperature, phase ratio, secondary phase precipitation temperature, and phase transformation process of the material. Combine the strengthening and toughening mechanism and corrosion resistance mechanism of the material to provide specific material composition screening criteria, so as to obtain the optimized composition range.
[0054] 4) Conduct high-throughput experimental verification according to the calculation results in step 3) to further verify and optimize the composition range.
[0055] Use the composition optimization results determined in step 3) to carry out high-throughput experiments such as smelting, hot rolling, cold rolling, and heat treatment quickly and at low cost using a small-scale vacuum induction melting furnace, obtain the actual experimental data of the hot stamping process on the mechanical properties and pitting corrosion properties, and further verify and optimize to obtain the final composition system and process plan that meet the user's requirements.
[0056] The following further elaborates on this solution through specific embodiments.
[0057] Table 1 shows the chemical compositions of the steels in Examples 1-5; Table 2 shows the formation temperatures of each key phase calculated using the Thermo-Calc calculation software package; Table 3 shows the mechanical properties and pitting corrosion properties of the steels finally obtained in Examples 1-5.
[0058] Table 1 Chemical Compositions of Examples (wt / %)
[0059] Example C Si Mn Cr N P S V Nb Als 1 0.08 0.08 0.8 13 0.04 0.011 0.005 0.12 0.03 0.04 2 0.05 0.05 1.8 14 0.08 0.008 0.006 0.15 0.1 0.04 3 0.09 0.09 0.9 12.6 0.05 0.012 0.004 0.11 0.04 0.035 4 0.1 0.1 1 13 0.06 0.011 0.005 0.09 0.05 0.02 5 0.07 0.11 1.2 12.8 0.07 0.012 0.004 0.1 0.06 0.04 6 0.06 0.12 1.2 13.2 0.08 0.009 0.005 0.08 0.05 0.03 7 0.13 0.12 1.8 13.9 0.06 0.008 0.003 0.07 0.08 0.025 8 0.16 0.48 1.5 13.8 0.08 0.01 0.005 0.05 0.05 0.045 9 0.18 0.04 0.8 13.3 0.08 0.006 0.004 0.12 0.09 0.045 Comparative Example 0.17 0.5 0.6 13.8 - 0.008 0.004 - - 0.03
[0060] Table 2 Formation Temperatures of Characteristic Parameters in Hot-Stamped Stainless Steel (°C)
[0061]
[0062]
[0063] In the examples, the components were used to prepare ingots using a 1 kg vacuum induction melting furnace, and then 1.5 mm thick cold-rolled plates were prepared through hot rolling - pickling - cold rolling. After that, hot forming tests were carried out. The specific parameters were: the austenitizing heating temperature was 950 °C, the holding time was 5 - 6 min, and then it was transferred to the hot stamping die within 8 s, stamped, held under pressure for 6 - 10 s, and taken out after cooling to below 150 °C.
[0064] Table 3 Mechanical Properties and Pitting Corrosion Properties of Hot-Stamped Stainless Steel
[0065] Example Rp0.2 / MPa Rm / MPa A50 / % <![CDATA[Pitting potential / V SCE > 1 1115 1564 5 0.08 2 1076 1501 6.0 0.10 3 1123 1640 6.5 0.07 4 1285 1665 7.2 0.08 5 1317 1719 5.9 0.09 6 1293 1698 5.5 0.1 7 1318 1754 5.0 0.07 8 1305 1738 4.5 0.06 9 1426 1786 3.0 0.05 Comparative Example 886 1350 8.5 Activation system, no pitting potential
[0066] As can be seen from the data in Table 1 - Table 3, for the technical solution adopted in the present invention, the tensile strength of the prepared steel plate is ≥1500 MPa, and the pitting potential is ≥0.05 V SCE , which is a hot - stamping stainless steel with a tensile strength reaching the 1500 MPa level and having good corrosion resistance.
Claims
1. A 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts, characterized in that: The chemical composition of the steel by weight percentage is: C: 0.05% ~ 0.20%, Si: 0.05% ~ 0.50%, Mn: 0.50% ~ 2.00%, P ≤ 0.020%, S ≤ 0.010%, Cr: 12.0% ~ 15.0%, V: 0.05% ~ 0.15%, Nb: 0.02% ~ 0.10%, Ni ≤ 1.00%, Cu ≤ 0.30%, Al < 0.05%, N: 0.01% ~ 0.10%, and the balance is Fe and unavoidable impurity elements.
2. The 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts according to claim 1, characterized in that: The Cr equivalent in steel, Creq=Cr%+Mo%+1.5×Si%+0.5×Nb%+5×V%+3Al, is controlled within 15.0%.
3. The 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts according to claim 1, characterized in that: The Ni equivalent Nieq in steel = Ni% + 30×C% + 0.5×Mn% + 0.3×Cu% + 25N% + Co% is controlled within 8.0%.
4. The 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts according to claim 1, characterized in that: The δ phase formation temperature in the steel is ≥1100℃, and the Nb (C, N) solid solution temperature is ≥1100℃.
5. The 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts according to claim 1, characterized in that: Cr in steel 23 C6 and Cr x N y The solution temperature is ≤950℃.
6. The 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts according to claim 1, characterized in that: The solidification temperature of V (C, N) in steel is higher than 870℃.
7. The 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts according to claim 1, characterized in that: The tensile strength of the stainless steel plate is ≥1500MPa, and the pitting potential is ≥0.05V SCE .
8. A method for rapid screening of components by integrating thermodynamic calculations and high-throughput testing, characterized in that: The method is used to develop 1500MPa grade corrosion-resistant stainless steel for hot stamping automobile parts as claimed in any one of claims 1 to 7, and specifically comprises the following method steps: 1) By analyzing the application scenario requirements of steel grades, a benchmark product system is collected according to product characteristics as a performance optimization benchmark; the target steel grade is mainly martensitic, with martensitic stainless steel 1Cr 13 , 2Cr 13 As a benchmark, the corrosion resistance is improved by microalloying with N, Nb and V; 2) For the component system determined in step 1), the thermodynamic software Thermo-Calc is used to call the iron-based multi-component thermodynamic database TCFE10 to calculate the phase diagram under the relevant components; the thermodynamic calculation method and Schaeffler phase diagram are used to predict the phase composition and performance enhancement mechanism of the material under different temperature and composition conditions, evaluate the coupling of mechanical properties and application performance of different components, and preliminarily determine the material components; 3) Based on step 2), the key phases that affect mechanical properties and application performance are determined and named as characteristic parameters. Then, the dynamic simulation software DICTRA is used to calculate the phase transition temperature, phase ratio, second phase precipitation temperature, and phase transition process of the material based on the phase diagram thermodynamic database TCFE10 and the diffusion dynamics database MOBFE5. Combined with the material's toughness mechanism and corrosion resistance mechanism, specific material composition screening criteria are provided to obtain the optimized composition range; 4) Using the composition optimization results determined in step 3), a vacuum induction melting furnace is used to carry out high-throughput experiments on smelting, hot rolling, cold rolling, and heat treatment to obtain actual experimental data on the effects of hot stamping process on mechanical properties and pitting corrosion properties, and further verify and optimize the final composition system.
Citation Information
Patent Citations
Low temperature hot stamping automobile part and hot stamping technology thereof and manufacturing method of low temperature hot stamping automobile part
CN106906421A
Hot stamping high strength steel automobile body covering part and manufacturing method and system thereof
CN109433960A
Preparation method of ultrahigh-strength high-plasticity hot stamping forming steel
CN113106338A
Martensitic stainless hot rolled steel sheet, manufacturing method of disc brake rotor using the steel sheet
JP2019173087A
Cited By
1500MPa-grade thick-specification hot stamping plate with excellent corrosion resistance and manufacturing method of 1500MPa-grade thick-specification hot stamping plate
CN120249829A